2018
DOI: 10.1017/s1742058x18000218
|View full text |Cite
|
Sign up to set email alerts
|

Intersectionality, Cognition, Disclosure and Black LGBT Views on Civil Rights and Marriage Equality

Abstract: Intersectionality has contributed to the ongoing deconstruction of dichotomous and essentializing categories of identity and oppression. As some scholars have noted, however, intersectionality has debunked a sociobiological, single-node paradigm and unintentionally codified a deterministic form of social cognition. I suggest one mechanism for understanding how to untangle this intersectional dilemma: disclosure practices. Disclosure of stigmatized statuses can illuminate how macro level inequalities manifest i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Five studies explicitly examined racial/ethnic minority identities as a factor in individuals’ perceptions of same-sex marriage; one qualitative study focused exclusively on Black individuals in the U.S. [ 72 ] and the other four examined differences by race/ethnicity [ 64 , 66 , 67 , 73 ]. McGuffy [ 72 ] conducted in-depth interviews with 102 Black LGBT individuals about their perceptions of marriage as a civil rights issue before and after same-sex marriage was recognized nationally in the U.S. The study found that intersecting identities and experiences of discrimination related to racism, homophobia, and transphobia influenced personal views of marriage.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies explicitly examined racial/ethnic minority identities as a factor in individuals’ perceptions of same-sex marriage; one qualitative study focused exclusively on Black individuals in the U.S. [ 72 ] and the other four examined differences by race/ethnicity [ 64 , 66 , 67 , 73 ]. McGuffy [ 72 ] conducted in-depth interviews with 102 Black LGBT individuals about their perceptions of marriage as a civil rights issue before and after same-sex marriage was recognized nationally in the U.S. The study found that intersecting identities and experiences of discrimination related to racism, homophobia, and transphobia influenced personal views of marriage.…”
Section: Resultsmentioning
confidence: 99%
“…Although transgender and nonbinary individuals were included in eight studies, five provided only descriptive information and only three described any unique findings from transgender study participants. For example, McGuffey [ 72 ] found that transgender individuals who identified as heterosexual described same-sex marriage rights as less relevant than issues of gender identity and expression and Hull found that cisgender sexual minority men generally expressed more enthusiasm about marriage than both cisgender women and transgender individuals [ 69 ]. Transgender and nonbinary individuals who perceive positive impacts of equal marriage rights may still experience challenges in navigating heteronormative and cisnormative expectations [ 72 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And, last, this study adds to intersectional theory by focusing on the ways in which interconnecting structural inequalities shape cognitive frames and meaning-making apparatuses (McGuffey, 2018). I do not suggest this more cognitive approach as a replacement of, but rather as an addition to, intersectional approaches.…”
Section: Discussionmentioning
confidence: 99%
“…This contextual information is important for an account analysis because it draws attention to the ways in which personal accounts are “social texts” (Schou & Hewison, 1998), which are both constructed by social constraints and, simultaneously, constructs social constraints (Davis, 2005; McKenzie-Mohr & Lafrance, 2011). Second, a longer discussion of a small number of cases is necessary to clarify the connection between individual agency, the cultural tools used in drawing sexualized moral boundaries, defensive othering, and the social control and closure emphasized in appraisal processes (Chen, 1999; McGuffey, 2018). Thus, the demeanor and disposition of the participants are underscored to reveal the ways in which individual agency in accounting practices are articulated by survivors as they navigate their social and psychological terrain after sexual assault.…”
Section: Methodsmentioning
confidence: 99%